(untitled) (Research, Society and Development, 2025)
Women’s futsal is a high-intensity sport characterized by intermittent actions, rapid changes of direction, and constant accelerations and decelerations, demanding high physical, technical, and tactical performance from the athletes. Each position on the court presents specific physical and functional demands that directly influence the body profile of the players. Therefore, this study aims to analyze the differences in body composition among female futsal athletes according to their tactical positions (wing, defender, pivot, and goalkeeper). This is an observational and cross-sectional study involving 20 athletes from the Associação Desportiva de Futsal do Distrito Federal (ADEF). Anthropometric and body composition assessments were performed, including weight, height, skinfold thickness, fat mass, and lean mass, according to the positions played on the court. The data were statistically analyzed to identify significant differences between the groups. Wing players showed lower percentages of body fat and body mass, while pivots and defenders showed higher values ​​of lean and total mass, and goalkeepers exhibited an intermediate profile. The results aim to contribute to training strategies and nutritional prescriptions specific to each position, optimizing the performance and health of female athletes.